Investigating the Effects of Authentic Activities on Foreign Language Learning: A Design-based Research Approach - Ozverir, Ildeniz; Osam, Ulker Vanci; Herrington, Jan (Int Forum Educational Technology & Soc, Natl Taiwan Normal Univ, 2017)
Achieving communicative competency in English classes has been a key goal in contexts where English is taught as a foreign language (EFL). During this process, however, integrating the difficulty and complexity of real life tasks into classroom teaching has often been disregarded. Lack of opportunities for authentic language use often results in learners' gaining extensive knowledge about the target language (know what) while they are weak in using the language in a meaningful way (know how). Accordingly, while learners can talk about grammar rules, they usually fail to use these rules for real communicative purposes in unstructured genuine settings. The present study employed a design-based research approach to investigate the use of authentic activities in EFL classes. For this purpose, an e-leaming environment was created based on initial design principles of authentic activities and implemented in three pre-university level EFL classes in North Cyprus in two research cycles. Data were collected through semi-structured interviews, work samples, and observations. In accordance with the findings and continuous literature review, 11 design principles were derived from the initial design principles for the EFL context in order to facilitate competency-based foreign language use.
Keywords: Authentic learning; Authentic tasks; Foreign language education; Task-based language learning; Design-based research